Molecular characterization of Sweet potato feathery mottle virus and sweet potato yield loss due to its infection - GUSTI NGURAH ALIT SUSANTA WIRYA; DEWA GEDE WIRYANGGA SELANGGA; LISTIHANI LISTIHANI; I GEDE RAI MAYA TEMAJA; I PUTU SUDIARTA (Society for Indonesian Biodiversity, 2024)
Abstract. Wirya GNAS, Selangga DGW, Listihani L, Temaja IGRM, Sudiarta IP. 2024. Molecular characterization of Sweet potato feathery mottle virus and sweet potato yield loss due to its infection. Biodiversitas 25: 2355-2362. Sweet potatoes are one of the main sources of carbohydrates for Balinese.